Hidden challenges to happiness: A cross-sectional study of Western Maharashtra, India - Alka Dilip Gore; Randhir V. Dhobale; Vivek B. Waghachavare; Girish B. Dhumale (Archives of Mental Health)
Background and Objectives: Individual happiness and well-being are the most essential components of quality of life. For the last few years, the United Nations General Assembly has annually published the World Happiness Report, and the ranking of India has repeatedly fallen to an alarming level where the country’s position remains below 100 nations in these surveys. Hence, this study was carried out to uncover the associated sociodemographic and lifestyle-related factors for happiness and well-being in the general population of Sangli district, Western Maharashtra, India. Materials and Methods: A cross-sectional study was conducted using a questionnaire among willing adults in the Sangli district. Section A regarding the sociodemographic data; Section B is the evaluation of lifestyle-related factors; and Section C contains a 29-item Oxford Happiness Questionnaire scale for assessing personal happiness. Microsoft Office 365 and SPSS-22 software were used to analyze data. Results: Out of the 679 participants, 61.9% of 420 people were not happy or somewhat unhappy, 34% were satisfied, and only 4.1% were happy. Participants were significantly unhappy despite having reliable and trustworthy friends and even after taking a complete rest. Multivariate analysis showed age, per capita income, occupation, and education are significant predictors of the happiness index score. Interpretation and Conclusion: People did not experience happiness after several favorable situations. Happiness is complex and subjective; it is very challenging to capture fully with a single index or questionnaire.